(untitled) (E Global Congress, 2025)
The 21st century world economy globalization under the circumstances deep structural to changes face In particular , developing countries in front of standing the most important from tasks one is economic growth stable pace provide with one in a row , networks in the section modern investment streams attraction to grow through them diversification and modernization from doing This view is from the perspective of Uzbekistan Republic for village farm field strategic importance profession provider network as confession This is industry country gross internal of the product noticeable part forms, millions population life style and income to the source has become, as well as food safety in providing, social stability in storage and export potential in development important role plays.